2004
DOI: 10.1021/ja039228n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Monodisperse Oligofluorene-Functionalized Truxenes:  Highly Fluorescent Star-Shaped Architectures

Abstract: This paper describes the strategy toward novel monodisperse, well-defined, star-shaped oligofluorenes with a central truxene core and from monofluorene to quaterfluorene arms. Introduction of solubilizing n-hexyl groups at both fluorene and truxene moieties results in highly soluble, intrinsically two-dimensional nanosized macromolecules T1-T4. The radius for the largest oligomer of ca. 3.9 nm represents one of the largest known star-shaped conjugated systems. Cyclic voltammetry experiments reveal reversible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
262
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(271 citation statements)
references
References 49 publications
9
262
0
Order By: Relevance
“…Although the signal at 7.55-7.45 ppm is an expected one and can be easily assigned to the two protons in the ortho position to a bromo end group (cf. Scheme 1, R 1 or R 2 ¼ Br), 49 the signals at 7.40-7.30 and 6.88-6.80 ppm are unexpected. The first unanticipated signal can be assigned to three protons of a hydrogen-terminated PF6 (cf.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the signal at 7.55-7.45 ppm is an expected one and can be easily assigned to the two protons in the ortho position to a bromo end group (cf. Scheme 1, R 1 or R 2 ¼ Br), 49 the signals at 7.40-7.30 and 6.88-6.80 ppm are unexpected. The first unanticipated signal can be assigned to three protons of a hydrogen-terminated PF6 (cf.…”
Section: Resultsmentioning
confidence: 93%
“…The first unanticipated signal can be assigned to three protons of a hydrogen-terminated PF6 (cf. Scheme 1, R 1 or R 2 ¼ H), 49 and the second can be assigned to two protons of PF6 featuring a hydroxy end group (cf. Scheme 1, R 1 or R 2 ¼ OH).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the MALDI-TOF MS spectrum of G0-4-2, in which the sharp molecular ion peak at m/z = 6246 Da (calcd: m/z = 6250 Da) and another signal corresponding to dehexylated fragment [MÀC 6 H 13 ] + (calcd: m/z = 6165 Da, found: m/z = 6161 Da) was clearly observed, which was similar to those of other truxene derivates. [22] All these results clearly indicated the molecular identity and purity of G0-4-2. The thermal properties of our dendrimers were analyzed by thermal gravimetric analysis (TGA).…”
Section: Synthesis and Characterizationmentioning
confidence: 72%
“…[26] This result shows that the highly fluorescent truxene moieties in the dendritic structure effectively influence the optical properties of the OTV segments. [22] The improved fluorescence quantum yields are beneficial to photoinduced electron transfer efficiency in organic solar cells, in which the donor material was mixed with fullerene derivatives. [27] Thus, our design strategy might provide a general strategy to improve the performance of organic solar cells based on OTVs and other nonluminescent molecules.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…We found that a modifi ed Suzuki protocol using Ba(OH) 2 as a base gave almost quantitative yields for T1Si-T4Si . To increase the yield of the oligofl uorene-truxene core compounds T1Si-T4Si in both Suzuki and Negishi coupling protocols, it was essential to increase the equivalents of the precursor arms (boronic acid or organozinc compound) relative to the core compound 2 or T2Br to a ratio of 5: 1 (instead of the 3.45: 1 ratio that was used in our original publication [ 6 ] ).…”
Section: Discussionmentioning
confidence: 99%